2023
DOI: 10.1161/strokeaha.122.041932
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Stroke Risk and Its Predictors in Asymptomatic Moyamoya Disease: Asymptomatic Moyamoya Registry (AMORE)

Abstract: Background: Long-term outcomes are unknown in patients with asymptomatic moyamoya disease. In this report, we aimed to clarify their 5-year risk of stroke and its predictors. Methods: We are conducting a multicenter, prospective cohort study (Asymptomatic Moyamoya Registry) in Japan. Participants were eligible if they were 20 to 70 years, had bilateral or unilateral moyamoya disease, experienced no episodes suggestive of TIA and stroke; and were functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition, radiological observations were also similar, as stenotic characteristics of moyamoya disease with donuts-like concentric pattern (Kim et al, 2013;Ya et al, 2020) were also reported in TKI-associated CVS (Hirschbuehl et al, 2019;Suzuki et al, 2019) and large vessel stenosis of the leg (Hirschbuehl et al, 2019), which differentiate from the typical eccentric atherosclerosis. Furthermore, clinical manifestations of moyamoya disease may also resemble the present TKI-associated case, featuring an extended asymptomatic period (Kuroda et al, 2023) possibly due to resistance to infarctions, atypical infarct areas irrespective of anatomical perfusion areas, and confined infarctions in gray matter (known as "gyral pattern, " especially in younger patients; Cho et al, 2011;Kuroda et al, 2023). Added to these similarities, some TKI-associated CVS was reported to be affected by the genetical abnormality (ring finger protein 213) of moyamoya disease (Uemura et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, radiological observations were also similar, as stenotic characteristics of moyamoya disease with donuts-like concentric pattern (Kim et al, 2013;Ya et al, 2020) were also reported in TKI-associated CVS (Hirschbuehl et al, 2019;Suzuki et al, 2019) and large vessel stenosis of the leg (Hirschbuehl et al, 2019), which differentiate from the typical eccentric atherosclerosis. Furthermore, clinical manifestations of moyamoya disease may also resemble the present TKI-associated case, featuring an extended asymptomatic period (Kuroda et al, 2023) possibly due to resistance to infarctions, atypical infarct areas irrespective of anatomical perfusion areas, and confined infarctions in gray matter (known as "gyral pattern, " especially in younger patients; Cho et al, 2011;Kuroda et al, 2023). Added to these similarities, some TKI-associated CVS was reported to be affected by the genetical abnormality (ring finger protein 213) of moyamoya disease (Uemura et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…The Asymptomatic Moyamoya Registry (AMORE) study, the largest prospective cohort study for asymptomatic MMD, is in progress. 20 In that study, questionable (Q) cases in which the stenosis existed only in the proximal portion of the MCA were enrolled, as well as typical MMD cases. The AMORE study group mentioned that the Q cases may be almost identical to isolated MCA disease, and we speculate that a Q case identical to T-MCA may be defined as a variety of isolated MCA disease with NVF.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the long-term prognosis of conservative management for adult patients with MMD are limited. Some studies [17][18][19][20][21][22] have described the outcomes of conservative treatment for patients with asymptomatic or hemodynamically stable MMD. In a series of 113 adult patients with MMD, 17 the disease progression rate was reported to be approximately 20% over 6 years.…”
Section: Management Of Asymptomatic MMD In Adultsmentioning
confidence: 99%
“…The reported annual stroke rate in patients with conservatively managed adult MMD is 3.2% to 15.0%. [18][19][20][21] In a recent multicenter study in Japan with 103 asymptomatic adult patients with MMD, 22 the annual risk of stroke was 1.0% in the first 5 years, predominantly hemorrhage in nature. In the present study, the annual rates of HS and IS were 1.21 and 0.56 per 100 person-years, respectively, in patients with asymptomatic MMD and conservative management (eTable 8 in Supplement 1).…”
Section: Management Of Asymptomatic MMD In Adultsmentioning
confidence: 99%